LONERGAN, THE AIMS OF JESUS, AND SOCIAL MEMORY - Henderson, Ian (Science et Esprit, 2023)
This article seeks to relate two stories from the field of Historical Jesus Research. The first story tells how the thought of Bernard Lonergan was brought by the work of Ben F. Meyer to influence the work of key figures in Historical Jesus Research (notably J.D.G. Dunn and N.T. Wright –and less directly E.P. Sanders). The second story is that of the redefinition of Historical Jesus Research that is ongoing today in the work of newer scholars (for example, Chris Keith, Jens Schröter, Anthony LeDonne), seeking to surmount the mechanical, over-sceptical criteriology of post-war scholarship and embracing new studies in personal cognition, religious experience and the collective processes of social memory. I ask whether this second story should become a new moment for Lonergan’s thought to exercise a positive influence on New Testament Studies.